Meta-Analysis Study: Effectiveness of Play Therapy to Reduce Children's Aggressiveness - Alfath, Esa Arsyiatul; Zalki, Riki; Chusniyah, Tutut (Personifikasi: Jurnal Ilmu Psikologi, 2025)
Child aggression has become an increasing problem in recent years. Children who exhibit aggressive behavior tend to have difficulty controlling their emotions, get angry quickly and are often involved in conflicts with peers and family members. If not adequately addressed, this aggressiveness can negatively impact a child's social, emotional, and academic development, potentially leading to more severe behaviors later in life. One proven effective way to reduce aggressiveness in children is through play therapy. In this therapy, children can process emotions that are difficult to understand or express verbally, including anger and frustration, which often trigger aggressiveness. The study aims to see play therapy's effectiveness in reducing children's aggressiveness. The method used in this study is meta-analysis, in which researchers reviewed 14 selected journals based on predetermined characteristics. The analysis results show that play therapy has a significant effect size and effectively reduces aggressiveness in children. Further studies could explore the long-term impact of play therapy on children's aggressiveness across different age groups and cultural backgrounds, as well as its effectiveness when combined with other therapeutic interventions.